Thinking about two fusion work in the new situation - Mingfeng HUANG (Dianxin kexue)
First of all,the challenges of our country's economy and manufacturing industry were introduced.Secondly,the connotation of the integration of the two and the related concepts,such as intelligent manufacturing,the internet and industrial integration,were detailed presented,and finally suggestions on the implementation of the integration of the two were put forward.